Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1055/s-0030-1262504
|View full text |Cite
|
Sign up to set email alerts
|

Swallow–Breath Interaction and Phase of Respiration with Swallow during Nonnutritive Suck among Low-risk Preterm Infants

Abstract: This study describes swallow-breath interaction and phase of respiration with swallow during nonnutritive suck (NNS) in low-risk preterm infants. Suckle and swallow, thoracic motion, and airflow were measured in 16 infants during NNS. Logistic regression models were used to describe swallow-breath interaction and phase of respiration with swallow. One hundred seventy-six swallows occurred in 35 NNS periods. Swallow-breath interaction occurred as: central apnea (CA), obstructive apnea (OA), or attenuated respir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 53 publications
3
25
0
Order By: Relevance
“…16 Additionally, birthweight is related to improved coordination of breathe, suck, swallow leading to more efficient feeding. 17 Matsubara et al (2005) compared sucking bursts for eight VLBW with seven full-term infants and reported that VLBW infants exhibited lower sucking pressures and shorter sucking bursts, reducing feeding efficiency. 10 Our findings of the negative association between lower birthweight and longer oral feeding progression supports previous findings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…16 Additionally, birthweight is related to improved coordination of breathe, suck, swallow leading to more efficient feeding. 17 Matsubara et al (2005) compared sucking bursts for eight VLBW with seven full-term infants and reported that VLBW infants exhibited lower sucking pressures and shorter sucking bursts, reducing feeding efficiency. 10 Our findings of the negative association between lower birthweight and longer oral feeding progression supports previous findings.…”
Section: Discussionmentioning
confidence: 99%
“…16 Larger birthweight was significantly associated with more coordinated breath, suck, and swallow cycles. 17 Infants with higher birthweights swallow at either mid-expiration or during apnea which was shown to significantly reduce the risk of aspiration. 17 However, premature infants with very low birthweight (VLBW) exhibit a significantly shorter sucking cycle length (amount of time from the peak of one suck to the peak of the next suck) and low sucking pressures (measured in mmHg as the strength of the suck – e.g.…”
Section: Review Of Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Oral feeding in preterm infants with BPD is challenging because preterm infants already have respiratory problems such as decreased minute ventilation. Minute ventilation is even decreased during oral feeding [16,17]. Apnea or desaturation events during feeding is more frequent in infants with BPD compared to that in those without BPD.…”
Section: Discussionmentioning
confidence: 99%
“…Reynolds et al studied swallowing-breathing interactions in 16 preterm newborns over a period of several weeks. 18 They found that, initially, the majority of nonnutritive swallows (NNS) occurred primarily during inhalation-exhalation transition points where the authors postulated that airflow was thought to be minimal. However, as gestational age increased, NNS swallows were more frequently timed with early exhalation.…”
Section: Breast-versus Bottle-feedingmentioning
confidence: 99%